CLUSTER ANALYSIS OF FINANCIAL BEHAVIORS AND PREFERENCES AMONG THE BOTTOM OF THE PYRAMID GROUP - Dewi Saraswati; Dian Kusumaningrum (Jurnal Manajemen dan Kewirausahaan, 2019)
This study investigates the financial behavior and preferences of the bottom of the pyramid (BOP) group, and thus, contributes to the financial inclusion demand-side literature. A survey of 100 households was conducted. A cluster analysis was used to analyze the data and portray the characteristics of the BOP. Further analysis was conducted using chi-square and ANOVA tests. The results reveal three sub-groups within the BOP which consists of the very low, low, and medium. Financial behaviors are found to be indifferent among the sub-groups, except for savings allocations and financial planning. Households with a better economic condition are found to have a higher attention to use banking services. The financial literacy category indicates different attitudes in conducting long-term financial planning and service preferences. This result implies that financial literacy and adequate financial products are beneficial towards the financial inclusion of the BOP group.